2015
DOI: 10.1021/jp512400c
|View full text |Cite
|
Sign up to set email alerts
|

Fast Surface Crystallization of Molecular Glasses: Creation of Depletion Zones by Surface Diffusion and Crystallization Flux

Abstract: Molecular glasses can grow crystals much faster at the free surface than in the interior. A property of this process is the creation of depressed grooves or depletion zones around the crystals on the initially flat amorphous surface. With scanning electron microscopy and atomic force microscopy, we studied this phenomenon in indomethacin, which crystallizes in two polymorphs (α and γ) of different morphologies. The observed depletion zones are well reproduced by the known coefficients of surface diffusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…This supports the notion that surface crystal growth is controlled by surface diffusion [ 34 , 35 ]. This conclusion is further supported by the fact that surface crystals grow upward and laterally without deep penetration into the bulk and are surrounded by grooves created by the surface motion of molecules toward the crystal [ 36 , 37 ].…”
Section: Polyelectrolyte Coatingmentioning
confidence: 99%
“…This supports the notion that surface crystal growth is controlled by surface diffusion [ 34 , 35 ]. This conclusion is further supported by the fact that surface crystals grow upward and laterally without deep penetration into the bulk and are surrounded by grooves created by the surface motion of molecules toward the crystal [ 36 , 37 ].…”
Section: Polyelectrolyte Coatingmentioning
confidence: 99%
“…The surface crystal growth rate was measured by tracking the crystals spontaneously nucleated at the free surface. Previous studies have reported that -IMC exhibits a much faster crystal growth at the free surface than in the interior (Hasebe et al, 2014(Hasebe et al, , 2015Musumeci et al, 2016). In this work, we carefully measured the growth kinetics in the supercooled liquid state, either at the free surface or in the bulk, by tracking the speed at which the growth front advanced.…”
Section: Bubble-induced Crystal Growthmentioning
confidence: 99%
“…For this rapid surface crystal growth, the crystal could grow edgewise and extend tens to hundreds of nanometres above the amorphous film (Sun et al, 2011). Another intriguing property of surface crystal growth is the formation of depletion zones in the amorphous matrix near the crystal growth frontier (Hasebe et al, 2014(Hasebe et al, , 2015. Recent studies have revealed that fast surface crystal growth is related to the extremely fast molecular diffusion at the free surface (Yu, 2016;Zhu et al, 2011;Huang et al, 2017;Brian & Yu, 2013;Zhang et al, 2015;Chai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have shown that glasses exhibiting van der Waals forces (vdW glasses) exhibit faster surface diffusion than glasses with significant hydrogen bonding (network glasses). Surface mobility was found to have a central role in the stability of molecular glasses, with surface crystal growth occurring laterally and upward, not down into the bulk (Hasebe et al 2015). Glasses with faster surface diffusion result in faster crystal growth, and result in depletion zones on the surface (Fig.…”
Section: Academic and Industrial Perspectives Of Amorphous Materialsmentioning
confidence: 99%